Kesiapan Koperasi Eksportir Kopi dalam Memenuhi Persyaratan Dokumentasi Regulasi Bebas Deforestasi Uni Eropa (EUDR) - Arwen Angelica; Akuat Supriyanto (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
The European Union Deforestation Regulation (EUDR), officially adopted by the European Union in 2023, has gained various responses from exporters, mainly due to quite demanding perception on regulation. This study focuses on the smallholder group (cooperatives and farmers), as among most impacted parties considering the financial constraints, knowledge limitation, and technical capacity. The main emphasis focuses on the challenges to comply EUDR’s documentation requirements, which include land use maps, sustainability certificates, land ownership documents, geolocation maps, proof of coffee land ownership, and the Supply Chain Traceability Report. This study aims to explore in depth the opportunities, barriers, and handling strategies adopted by exporting cooperatives. Primary data were collected through structured interviews with five cooperative representatives from various regions of Indonesia and analyzed using a thematic analysis method, referring to three main components of the Dynamic Capabilities Theory: Sensing, Seizing, and Reconfiguring. The outcome of this research presents internal and external strategic recommendations for cooperatives to prepare for the official implementation of the EUDR.